A randomized phase II trial of nab‐paclitaxel and gemcitabine with tarextumab or placebo in patients with untreated metastatic pancreatic cancer. (26th July 2019) - Hu, Zishuo Ian; Bendell, Johanna C.; Bullock, Andrea; LoConte, Noelle K.; Hatoum, Hassan; Ritch, Paul; Hool, Hugo; Leach, Joseph W.; Sanchez, James; Sohal, Davendra P. S.; Strickler, John; Patel, Ravindranath; et al.
Abstract: Purpose: Notch signaling dysregulation is implicated in the development of pancreatic adenocarcinoma (PDAC). Tarextumab is a fully human IgG2 antibody that inhibits Notch2/3 receptors. Patients and Methods: Aphase 2, randomized, placebo‐controlled, multicenter trial evaluated the activity of tarextumab in combination with nab‐paclitaxel and gemcitabine in patients with metastatic PDAC. Patients were stratified based on ECOG performance score and Ca 19‐9 level and randomized 1:1 to nab‐paclitaxel, gemcitabine with either tarextumab or placebo. Based on preclinical and phase Ib results suggesting a positive correlation between Notch3 gene expression and tarextumab anti‐tumor activity, patients were also divided into subgroups of low, intermediate, and high Notch3 gene expression. Primary endpoint was overall survival (OS) in all and in patients with the three Notch3 gene expression subgroups (≥25th, ≥50% and ≥75% percentiles); secondary end points included progression‐free survival (PFS), 12‐month OS, overall response rate (ORR), and safety and biomarker investigation. Results: Median OS was 6.4 months in the tarextumab group vs 7.9 months in the placebo group (HR = 1.34 [95% CI = 0.95, 1.89], P = .0985). No difference observed in OS in the Notch3 gene expression subgroups. PFS in the tarextumab‐treated group (3.7 months) was significantly shorter compared with the placebo group (5.5 months) (hazard ratio was 1.43 [95% CI = 1.01, 2.01]; P = .04). Grade 3 diarrhea and thrombocytopenia were more common in the tarextumab group. Conclusions: The addition of tarextumab to nab‐paclitaxel and gemcitabine did not improve OS, PFS, or ORR in first‐line metastatic PDAC, and PFS was specifically statistically worse in the tarextumab‐treated patients. Clinical trial registry no: NCT01647828. Abstract : A phase 2 study of tarextumab, an anti‐Notch 2/3 inhibitor, in combination with gemcitabine and nab‐paclitaxel in untreated advanced PDAC did not improve outcomes over standard therapy. PFS was statistically worse in the tarextumab‐treated group.